2013
DOI: 10.5607/en.2013.22.2.68
|View full text |Cite
|
Sign up to set email alerts
|

Role of Glial Cells in Axonal Regeneration

Abstract: Axonal regeneration is critical for functional recovery following neural injury. In addition to intrinsic differences between regenerative responses of axons in peripheral versus central nervous systems, environmental factors such as glial cells and related molecules in the extracellular matrix (ECM) play an important role in axonal regeneration. Schwann cells in the peripheral nervous system (PNS) are recognized as favorable factors that promote axonal regeneration, while astrocytes and oligodendrocytes in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 94 publications
1
15
0
Order By: Relevance
“…Previous studies have demonstrated that scarring represents a major barrier for axonal regrowth, and moderate inhibition of this process will enable axonal regrowth and improve functional recovery (34). In this study, fibrotic scar tissue rich in fibronectin and laminin formed at the lesion site after SCC, which is the key impediment for regenerate axons, containing axon growth inhibitory factors including chondroitin sulfate proteoglycans (CSPGs) (5).…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies have demonstrated that scarring represents a major barrier for axonal regrowth, and moderate inhibition of this process will enable axonal regrowth and improve functional recovery (34). In this study, fibrotic scar tissue rich in fibronectin and laminin formed at the lesion site after SCC, which is the key impediment for regenerate axons, containing axon growth inhibitory factors including chondroitin sulfate proteoglycans (CSPGs) (5).…”
Section: Discussionmentioning
confidence: 85%
“…Schwann cells, which are glial cells in the general peripheral nervous system (PNS), play an important role in tissue repair process after PNS injury 20 and are also a target for use in neural repair therapies. To determine if Schwann cells also responded to RAD288 and RAD289, Schwann cells were treated with a range of concentrations from 0.78 to 6.25 µM of RAD288 and RAD289 for 24 h. We observed that both natural products did not affect the viability of Schwann cells (p > 0.05) in comparison with the negative control.…”
Section: Resultsmentioning
confidence: 99%
“…Glial cells and molecules in the extracellular matrix (ECM) orchestrate axonal regeneration upon injury. Successful PNS axon regeneration is largely attributed to Schwann cell response via proliferation, migration, and remyelination (Toy and Namgung 2013). In parallel, in PNS neurons, multiple signaling pathways monitoring gene expression in the soma, together with pathways in the growth cone, control the balance of microtubule assembly, dynamics, and stabilization to achieve optimal axon growth (Glenn and Talbot 2013;Saijilafu et al 2013a,b).…”
Section: Lncrnas In Peripheral Nerve Injury (Pni)mentioning
confidence: 99%